A close fitt: reading Beowulf fitt II with the Andreas-poet. (December 2019) - Thomas, Daniel
Abstract: Connections between Andreas and Beowulf have been the subject of much scholarly discussion. This article contributes to this discussion by arguing that the account of the Mermedonians' discovery of and response to the loss of their prisoners in Andreas fitt X, which corresponds to chapters 22–3 of the poet's putative Latin source, has been deliberately recast in ways intended to recall the account in fitt II of Beowulf of Grendel's first attack on Heorot and the reactions of the Danish community. The connection argued for here is based not on verbal correspondences, but on embedded structural and thematic parallels. The Andreas -poet emerges as a careful and sophisticated reader, notable for their specifically literate and textual engagement with Beowulf. This observation has implications not only for our appreciation of the Andreas -poet's art, but also for the transmission of Beowulf and for our understanding of Old English poetic practices more generally.